Experimental study of fracture energy for foamed concrete - Nasrullah, Alsad (2021)
Foamed concrete has recently gained attention as an alternative material to normal concrete in structural engineering. As a structural component, foamed concrete has many advantages given its characteristics such as high strength with low density, good serviceability, and lightweight. Therefore, many studies have been investigated for their strength and mechanical properties. However, literature has shown that there is a lack of research on fracture energy of foamed concrete, which is the main parameter that governs damage and cracks mechanisms of any structural components. Therefore, the present study aims to experimentally investigate the fracture energy of foamed concrete using beam specimens with U-notch and V-notch through a three-point bending test. Fifty-two (52) foamed concrete beam specimens with 100 mm x 100 mm x 800 mm in length with a density of 1600 kg/m³ were cast. The foamed concrete compressive strength of approximately 9 to 10 MPa was achieved at 28 days. Of the fifty-two numbers of beam specimens, two beams were cast as control specimens (with no notches) whilst the forty-eight number of beam specimens was provided with various variables including different notch shapes (U and V-notch), different notch sizes (notch depth to notch opening ratio), and different offset ratios. From the three-point bending test, the peak load, loaddisplacement profile, and crack patterns for all the beam specimens were highly influenced by the various variables provided. From observation, beams with V-notch with its single corner edge tip and at offset ratio at 0.0 gave higher peak loads and consistent crack patterns compared to beams with U-notch. Increasing the offset ratio reduces the peak load and changes the crack patterns when a combination of shear and bending stress influences the tensile stresses hence the crack direction of the beam. The experimental fracture energy GF was determined from the classical Hillerborg’s model. Three other theoretical models from Bazant, CEB, and JCIS were selected for comparison. For beams with U-notch, Bazant and CEB overestimated its fracture energy by +11.58% and +24.18% whilst JCIS underestimated its result by -30.18%. Similar trends was observed for beams with V-notches when Bazant and CEB both overestimated by +13.33% and 24.48% but was again underestimated by JCIS at -29.16%. However, by modifying the factors from Bazant, CEB, and JCIS equations, a modified theoretical model to measure fracture energy for foamed concrete was successfully developed. This was validated when the modified Bazant, CEB, and JCIS model achieved high accuracy levels at +0.64%, +0.63%, and +1.24%.